Peningkatan Kompetensi Microcontroller Siswa SMK - Zaenal Arifin; Teguh Tamrin (University of Islam Malang, 2019)
The increased interest in students in the field of Electronic Control is influenced by many factors, with family backgrounds, relationships, future expectations, development of science and technology and teachers. The implementation of the Community Service Program Based on Development of Foster Schools in Manba'ul Huda Dukuhseti, Pati Vocational School with the activities in the form of training and assistance in the use of electronic and computer software skills as additional knowledge in developing HR capabilities. Student Competency Improvement Training Related to Electronic and Computer Control Systems, namely programming and Arduino Uno application to create a led light control that can function according to a program made by each student. Through Arduino Uno training this makes science more for students in deepening microcontrollers. Keywords: electronic control, software, Arduino Uno